2015
DOI: 10.1371/journal.pone.0145507
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hedgehog-Signaling Driven Genes in Prostate Cancer Cells by Sutherlandia frutescens Extract

Abstract: Sutherlandia frutescens (L) R. Br. (Sutherlandia) is a South African botanical that is traditionally used to treat a variety of health conditions, infections and diseases, including cancer. We hypothesized Sutherlandia might act through Gli/ Hedgehog (Hh)-signaling in prostate cancer cells and used RNA-Seq transcription profiling to profile gene expression in TRAMPC2 murine prostate cancer cells with or without Sutherlandia extracts. We found 50% of Hh-responsive genes can be repressed by Sutherlandia ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The mechanisms for these putative medicinal properties of S. frutescens have not been investigated extensively. We and others have reported that ethanolic and aqueous extracts of this plant possess anti-inflammatory and immuno-stimulatory activities, respectively 6,7 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The mechanisms for these putative medicinal properties of S. frutescens have not been investigated extensively. We and others have reported that ethanolic and aqueous extracts of this plant possess anti-inflammatory and immuno-stimulatory activities, respectively 6,7 .…”
Section: Introductionmentioning
confidence: 88%
“…However, the mechanism(s) by which S. frutescens may modulate health outcomes remains unclear. Recently, our group demonstrated that an ethanol extract of S. frutescens down-regulated 50% of Hedgehog-responsive genes in murine prostate cancer cells (i.e., TRAMPC2) 6 . Also, we have previously reported that extracts from Sutherlandia can diminish NF-κB, ERK, AP-1, and JAK-STAT1 signaling in macrophages and microglia cells [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…The short filtered sequencing reads that were acquired were mapped to the human genome by the TopHat2 and Subreads package; the featureCounts function was used to quantify the gene expression values. These gene expression values were then used to calculate the size of the library and dataset dispersion for the analysis of differentially expressed genes [15]. Differential gene expression was examined using the R/Bioconductor package edgeR and established by log fold change (LogFC) and false discovery rate (FDR) (LogFC ≥ 1 or ≤-1; FDR ≤ 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…Extracts of S. frutescens have shown antiproliferation and apoptotic effect in breast cancer cells and cervical cancer cells [ 180 182 ]. Its actual mechanism of action remains largely unknown but in vitro Sutherlandia represses Hedgehog-signaling pathway in murine prostate cancer cells [ 183 ] as well as key molecules in the PI-3 K pathway in colon cancer cells [ 184 ].…”
Section: African Herbs Used For Common Ncds Modulating Cyp450 or Pmentioning
confidence: 99%